P3.370 Daily Oral Emtricitabine/Tenofovir Pre-Exposure Prophylaxis and Prevention of HSV-2 Acquisition Among Heterosexual Men and Women. (13th July 2013) - Celum, C; Morrow, R; Donnell, D; Hong, T; Thomas, K; Fife, K; Nakku-Joloba, E; Mujugira, A; Baeten, J
Abstract : Background: Daily oral and pericoital tenofovir-based antiretroviral pre-exposure prophlyaxis (PrEP), reduced risk of HIV-1 acquisition in trials among high risk populations; oral emtricitabine(FTC)/tenofovir (TDF) received a label indication for HIV-1 prevention. Peri-coital dosing of 1% tenofovir gel also reduced the risk of acquisition of herpes simplex virus type 2 (HSV-2), by 51%. Tenofovir has anti-HSV-2 activity in vitro, although the EC90 is high. We conducted a randomised, placebo-controlled trial of daily oral TDF and FTC/TDF as PrEP among 4747 HIV-1 uninfected partners in of heterosexual serodiscordant partnerships from Kenya and Uganda (the Partners PrEP Study) and demonstrated FTC/TDF reduced HIV-1 acquisition by 75%. We performed a secondary analysis of HSV-2 acquisition among initially HSV-2 seronegative participants. Methods: We tested archived sera from baseline for HSV-2 by EIA (Focus) and HSV-2 Western blot. Among initially HSV-2 seronegative participants, HSV-2 seroconversion was assessed at the last study visit prior to unblinding the placebo arm in July 2011. Results: 528 participants on FTC/TDF (35%) and 481 participants on placebo (32%) were HSV-2 seronegative at baseline. Eighty-nine post-randomization HSV-2 seroconversions were observed: 37 among those assigned FTC/TDF (incidence 4.4/100 person-years) and 52 among those assigned placebo (incidence 6.6/100 person-years). Compared to placebo, FTC/TDF reduced HSV-2 acquisition by 35% (95% CI 1 to 58, p = 0.05). Anti-HSV-2 effects trended towards protection for both men and women. Case-cohort analysis of plasma tenofovir levels to determine efficacy by drug exposure and subgroup analysis by HSV-2 status of the HIV-1 infected partner are underway. Conclusions: Among African heterosexual men and women, daily oral FTC/TDF PrEP modestly reduced the risk of HSV-2 infection in the context of a study population with high adherence and for whom high efficacy against HIV-1 acquisition was demonstrated. Potential protection against HSV-2 in addition to HIV-1 could increase the public health benefits of PrEP.